The impact of the 2018 VAT rate increase on the South African tax policy on the zero rating of merit goods - von Berg, Danae (Department of Finance and Tax, 2021)
The 2018 Value-Added Tax (VAT) rate increase caused a national debate on the regressive nature of VAT and its impact on the poor. This study assessed whether an appropriate response is to include further zero-rated items and to analyse which items should be selected. This study confirmed that VAT is regressive, and the instruments used to address this issue is to either introduce the zero-rating of ‘merit goods' or to use cash transfers in a social grant system. Given that a significant portion of the South African government expenditure is already spent on the social grant system and has not yet resulted in a significant decline of income inequality, the appropriate response to the 2018 VAT rate increase is to expand the list of zero-rated items. This study performed an analysis on the South African spending patterns per income group to identify the food items most consumed by the poor. The notable items included; poultry, beef, aerated soft drinks, white bread and white sugar, however these items would result in a significant loss of tax revenue, which is an inherent issue with a zero-rating amongst others. As the purpose of the 2018 VAT rate increase was to address the significant fiscal budget deficits over the last few years it would not be rational to introduce a zero-rating which would effectively eliminate the tax revenue needed to balance the fiscal budget. The government's response was to include sanitary pads, cake wheat flour and white bread wheat flour be zero-rated, which do not result in such a significant tax loss. Therefore, the selection of items in the current South African economic environment would involve a balancing act between providing relief to the poor but not at the expense of a significant share of tax revenue.